Valuation and sustainable management of crop and livestock biodiversity: a review of applied economics literature - Drucker, Adam G.; Smale, Melinda; Zambrano, Patricia (International Food Policy Research Institute, 2005)
This paper is part of the follow-up to the workshop “Managing Agricultural Biodiversity for Sustainable Development” organized by the International Plant Genetic Resources Institute (IPGRI) for the CGIAR System-wide Genetic Resources Programme (SGRP) and hosted by the World Agroforestry Centre (ICRAF), Nairobi, Kenya (23-25 October, 2003, Nairobi, Kenya).